A new start-up law of pump turbines with misaligned guide vane devices. (August 2022) - Yang, Biao; Zhao, Lin; Zhao, Wei; Qin, Yankui; Wang, Renwei; Liu, Changyu
The frequency of high head pump turbines easily fluctuates under the low head no-load condition, which makes it difficult to achieve the synchronous grid connection. In this study, a new start-up strategy of linkage between misaligned guide vane (MGV) devices and conventional guide vanes is proposed, and the optimal arrangement scheme of MGV devices is selected through experiments. Based on the characteristic method, improved Suter transform and the characteristics of MGV devices, the calculation model of transition process is established. The simulated rotational speed of emergency shutdown process fits well with the field measured data. Under start-up conditions, the newly proposed control law can effectively reduce the fluctuation amplitude of frequency, draft tube inlet pressure and volute inlet pressure, and shorten the synchronization time. Additionally, the newly proposed law can significantly improve the no-load stability of the pump turbine under different head conditions, especially low head conditions.